The Impact of Product and Price on Purchasing Decisions: A Study at Daster Aradas Wholesale Store in Pontianak City - Syarif Irpandi; Sumiyati Sumiyati (SAINTIS Publishing, 2025)
This study aims to analyze the influence of product and price on consumers’ purchasing decisions at the Daster Aradas Wholesale Store in Pontianak City. This research employs an associative approach with a total sample of 100 respondents determined through purposive sampling. Data were collected through interviews and the distribution of questionnaires, supported by secondary data in the form of sales records from the period 2021 to 2023. The results of analysis indicate that product and price variables have a positive and significant effect on purchasing decisions; product and price simultaneously and partially affect purchasing decisions. Based on these findings, it is recommended that the Daster Aradas Wholesale Store continue to enhance the variety, design, and quality of its products, while maintaining a competitive and transparent pricing strategy to strengthen consumer loyalty and attract new customers. Future research is suggested to broaden the scope of variables by considering other factors such as promotional strategies, service quality, and the effectiveness of digital marketing in order to gain a more comprehensive understanding of the factors influencing consumer purchasing behavior in the retail clothing industry.